Revenue Forecast Errors in the European Union - Afonso, António (2014)
In this paper we assess the determinants of revenue forecast errors for the EU-15 between 1999 and 2012, based on the forecasts published bi-annually by the European Commission. Our results show that personal income rate changes increase the revenue forecast errors: for forecasts made in t for t, increases in the corporate tax rate implies a decrease in the revenue forecast errors, in t+1 and t+2. Moreover, an increase in GDP forecast errors decreases revenue errors, whereas an increase in the inflation error will increase revenue errors. GDP errors, minority governments, election year and corporate tax rate changes can be associated with optimistic revenue forecasts. On the other hand, yield, inflation errors and VAT tax rate changes are associated with more prudent forecast behaviour.